Contaminants, mutagenicity and toxicity in the surface waters of Kyiv, Ukraine. (June 2020) - Ho, Kay T.; Konovets, Igor M.; Terletskaya, Anna V.; Milyukin, Mykhailo V.; Lyashenko, Artem V.; Shitikova, Larisa I.; Shevchuk, Lyudmila I.; Afanasyev, Sergey A.; Krot, Yurii G.; Zorina-Sakharova, Kateryna Ye.; Goncharuk, Vladislav V.; Skrynnyk, Maksym M.; et al.
Abstract: Kyiv is Ukraine's capital and largest city. Home to 3 million people, this area has a rich history of agriculture and industry. The Dnieper River is Ukraine's largest river and it passes through the center of Kyiv. Little information on emerging and legacy compounds or their toxicity in the Dnieper River exists. For this investigation, water was sampled for PAHs, PCBs, metals and emerging contaminants including pharmaceuticals and personal care products. The effects of surface waters in the Dnieper were evaluated using the Ames, chronic and acute daphnia, and a ciliate ( Colpoda stennii ) assays. Concentrations of legacy and emerging contaminants were found in seven stations near the municipal water treatment plant (MWTP) and receiving waters. The MWTP appeared to remove some of the emerging contaminants, however the legacy compounds (PCBs and PAHs) were not affected by the MWTP and appeared to be more wide-spread indicating a number of sources to the Dnieper River. Acute and chronic toxicity were associated with the influent and effluent of the MWTP, however mutagenicity was noted in surface waters throughout the Dnieper River including upstream of the MWTP. This study provides the first snapshot of possible human health and ecological risks associated with surface waters of the Dnieper. More research on seasonal changes and sources of toxicity, mutagenicity and contaminants would aid in completing a more comprehensive risk assessment of surface waters of the Dnieper River. Highlights: Ukraine has modern industrial cities and productive agricultural areas. The Dnieper River passes through the center of the capital, Kyiv. Little to no information exists on the concentrations and effects of legacy and emerging contaminants in the Dnieper River as it passes through Kyiv. Concentrations of legacy and emerging contaminants were found in all stations near the municipal water treatment plant (MWTP) and receiving waters. Acute and chronic toxicity were associated with the MWTP influent and effluent of the, however mutagenicity was noted in surface waters throughout the Dnieper. This is the first study to examine the magnitude of mutagenicity and toxicity present in Kyiv's Dnieper River along with extensive monitoring of chemical concentrations.